Orphan works - Anechitoae, Constantin (Technium Social Sciences Journal, 2023)
Digitization, dissemination or publication of works or other objects protected by copyright or related copyright rights, in the conditions where the copyright holders are not identified or in the second situation when the holder, although identified, is not located represents a new institution by defining it as the institution of "orphan works". In the research we are undertaking, we intend to identify the status of "orphan work", which works have the status of "orphan work" and which category of works cannot acquire the status of "orphan work". In all situations, appropriate research activities are required to conduct a diligent search in good faith to verify the status of the work in question and to verify under what conditions a particular work has been declared an orphan work.